Formation of molecular wires on nanostructured KBr - Maier, Sabine; et al. (Journal of Physics: Conference Series, 2007)
The formation of molecular wires on a nanostructured KBr(001) substrate is observed by non- contact atomic force microscopy. Locally polarized cyano porphyrin molecules evaporated on this sample assemble in a linear fashion along straight pit edges forming one dimensional structures. © 2007 IOP Publishing Ltd.
Created from Fastlane, Scopus look-up